The Effect of SQ5R Learning Method and Learning Motivation on Students Reading Skills - Indah Fajri Hilmi; Anisah Anisah; Desvalini Anwar; Elfia Sukma (Postgraduate, University of Mataram, 2024)
This research is motivated by the results of a preliminary study conducted by researchers at the research location that students do not master reading skills. Based on these findings, researchers are interested in obtaining information about the influence of using the SQ5R learning method and learning motivation on the reading skills of class V students at UT SDN 05 Pasar Baru. This research to explain: (1) the effect of using the SQ5R learning method on the reading skills for class V students who have high learning motivation (2) the effect of using the SQ5R learning method on reading skills (3) the effect of using the SQ5R learning method on reading skills for class V students who have low learning motivation (4) interaction between the use of the SQ5R learning method and learning motivation. Base on the research results, it was found that (1) by the t test results obtained sig. (2-tailed) 0,000 < 0,05 (2) by the t test results obtained sig. (2-tailed) 0,005 < 0,05 (3) by the t test results obtained sig. (2-tailed) 0,017 < 0,05 (4) significance of the test results 0,988 > 0,05, so there is an interaction between the SQ5R learning method and learning motivation.